Efficacy of Certain Antimicrobial Chemicals against Tasar Silkworm Disease Causing Pathogens - Kumar, K.P. Kiran; Sinha, Ajit Kumar; Singh, G.P; Sahay, Alok (IJRDO -Journal of Computer Science Engineering, 2015)
Estimated crop loss due to Pebrine, Virosis, Bacteriosis and Muscardine is 20-25, 25-30, 10-15 and 2-5%, respectively in tasar culture. Different preventive methods by using chemical disinfectants, is the better option for the control of silkworm disease. Therefore, disease causing pathogens of tasar silkworm namely Cytoplasmic polyhedrosis virus (AmCPV), Nosema mylittansis, Penicellium citrinum and different types of bacteria were subjected for the in vitro and In vivo inactivation studies with four chemicals namely Sodium Silicate Pentahydrate (SSP), Tri-sodium orthophosphate (TSP), Benzalkonium chloride (BKC) and Didecyldimethylammonium chloride (DDC), which are known for the germicidal activity. In vitro results revealed that, 1.5-3% of TSP is capable in dissolution of AmCPV and suppression of bacterial and fugal pathogens at 2-5 minutes sterilization time. 1-3% of SSP has given good results in dissolution of Nosema mylittansis at 3-5 minutes. 1-5% of BKC and DDC have given best results in suppression of bacterial and fungal pathogens from 2-5 minutes sterilization time. In vivo, TSP treated lots have shown less mortality due to the various diseases except in pebrine disease when compared with other disinfectants treatments. In TSP treated batches, mortality percentage due to AmCPV, Pebrine spores, Bacteria and P. Citrinum recorded was 5%, 9%, 4% and 2%, respectively. SSP treated lots have shown low mortality due to Pebrine spore with 6%, where as mortality due to other diseases was higher than other disinfectant treatments. In the case of inoculated control mortality percentage was ranged from 53% to 98% where as in the case of health control no mortality due to the any diseases was found. In case of Virosis, percentile disease reduction, TSP occupied first place (94.90) followed by DDC (72.45), BKC (54.08) and SSP (46.94). SSP hold first rank in reduction of Pebrine disease (92.50). BKC and DDC have given moderate results in the suppression of all the diseases. The effective chemicals in the present study can be used for the formulation of broad spectrum disinfectant.